Implementasi Akuntansi Dana Titipan dalam Program Tabungan Haji di Bank Syariah Indonesia KCP Tegal Slawi - A. Fajar Mujahidin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Hajj savings are an important Islamic banking product designed to assist Muslims in preparing for hajj expenses in a systematic and Sharia-compliant manner. As a trust-based fund, hajj savings require proper accounting treatment to ensure transparency, accountability, and compliance with Sharia accounting standards. This study aims to analyze the implementation of trust fund accounting in the Hajj Savings Program at Bank Syariah Indonesia (BSI) KCP Tegal Slawi. This research employs a qualitative descriptive approach using observation, documentation, and interviews conducted during an internship period at the research location. The data were analyzed by comparing accounting practices applied by the bank with relevant Sharia accounting standards, particularly PSAK 105 and PSAK 101. The results indicate that the hajj savings at BSI KCP Tegal Slawi are managed under a mudharabah contract and are recognized as temporary syirkah funds rather than bank income. The processes of recognition, measurement, presentation, and disclosure have generally been implemented in accordance with Sharia accounting principles. However, limitations were found in the level of accounting understanding among operational staff. This study implies that strengthening Sharia accounting literacy among bank employees is essential to enhance accountability and maintain customer trust in managing hajj funds.